PERAN KOORDINASI PADA KOMUNITAS INTELIJEN DAERAH MEMBANGUN KETAHANAN WILAYAH STUDI DI KABUPATEN DEMAK - Armaidy Armawi (Universitas Gadjah Mada, 2014)
Permendagri No. 16 2011 on the Change on Permendagri No. 11 2006 on Regional IntelligenceCommunity shows the strategic value for the regional government to detect every regional potentialthreats. Therefore there is an anticipation to solve the developing problems.This research was done tofind out coordination role in regional intelligence community activities at Demak regency. This researchis qualitative descriptive. The data collecting in use is observation and interview. The Demak regionalintelligence community does its role due to the intelligence functions such as investigation, securityand support. Therefore coordination is a very important in every activity. Optimal coordination andcommunication in routineactivities and incidental meetings are needed to maximize intelligenceinformation meeting. Strategy to optimize Demak regional intelligence community role is needed toorganize it to face every potential threats in supporting regional government and its related elements toestablish regional resilience.